If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9+3=-2(3x-6)
We move all terms to the left:
9+3-(-2(3x-6))=0
We add all the numbers together, and all the variables
-(-2(3x-6))+12=0
We calculate terms in parentheses: -(-2(3x-6)), so:We get rid of parentheses
-2(3x-6)
We multiply parentheses
-6x+12
Back to the equation:
-(-6x+12)
6x-12+12=0
We add all the numbers together, and all the variables
6x=0
x=0/6
x=0
| -14+5=-3(x+8) | | 2y+1/y=3/2 | | -15+21=2(x+2) | | 1=6x+10-7x | | x/52=180/120 | | -7x+11=5 | | 2y-6*3=-6 | | 2y-6*2=-6 | | 9²=9n | | 2y-6*1=-6 | | 5(3x+5)=-44+54 | | –8c–7c=90 | | -t/8.5=4.4 | | 1/2(6x+4)=4x-9 | | -2(v-7)=-18 | | 34=35-4(23-s) | | 2a^2=14 | | –5=z+5 | | 28x+4+17x-4=180 | | 5x2–13x+6=0 | | 2=a−5 | | 2x+40=7x-25 | | a=0.125/2.5 | | 2x²≥98=0 | | x+180=112 | | 15=x-21 | | 3.4x-3.2=1.6x+1.12 | | -6q+7=-17 | | 2=6+4u | | 2x+100+80=180 | | 9x–4x+4=3x-16 | | 2r=-27+15 |